Effects of Social Capital, Financial Access, Innovation, Socioeconomic Status and Market Competition on the Growth of Small and Medium Enterprises In West Java Province - Herny Constantia Fanggidae; Sutrisno Sutrisno; Frits Oscar Fanggidae; Riko Mersandro Permana (The Es Accounting And Finance, 2023)
This study aimed to investigate the effects of social capital, financial access, innovation, socioeconomic status, and market competition on the growth of small and medium enterprises (SMEs) in West Java Province. A cross-sectional survey design was employed, and data were collected from 384 SMEs using a structured questionnaire. Descriptive statistics, correlation analysis, and regression analysis were used to analyze the data. The findings showed that social capital, financial access, innovation, socioeconomic status, and market competition had a significant positive effect on the growth of SMEs in West Java Province. The study contributes to the existing literature by providing empirical evidence on the relationship between these factors and the growth of SMEs.